Functionally Small Riemann Sums Fungsi Terintegral Henstock-Dunford pada [a,b] - Solikhin Solikhin; Sumanto Sumanto; Siti Khabibah (JURNAL SAINS DAN MATEMATIKA, 2015)
In this paper we study Henstock-Dunford integral on [a,b]. We discuss some properties of the integrable. We shall define functionally small Riemann sums (FSRS) and show that it is necessary and sufficient condition for function to be Henstock-Dunford integral on [a,b]. Keywords: Henstock-Dunford integral, Functionally small Riemann sums